Potential of bioactive compounds Piper betle L. as angiotensin converting enzyme inhibitors: molecular docking study and in silico analysis evaluation of physicochemical properties, drug-likeness, and toxicity - Agus Kurniawan; Ernawati Sinaga; Muhammad Hanafi; Puspa Dewi Narrij Lotulung; Syamsudin Abdillah (Faculty of Pharmacy, Universitas Pancasila, 2026)
Hypertension remains a major global health burden, with angiotensin converting enzyme (ACE) representing a central therapeutic target in blood pressure regulation via the RAAS. Although synthetic ACE inhibitors are clinically effective, their long-term use is frequently associated with adverse effects, motivating the search for safer alternative agents. Piper betle L. is a medicinal plant rich in diverse bioactive phytochemicals with reported cardiovascular benefits. This study aimed to systematically evaluate the ACE inhibitory potential of Piper betle leaf constituents using an integrated in silico approach. A total of 43 compounds were docked against human ACE (PDB ID: 1UZF) using the PLANTS algorithm, with protocol validation performed by captopril redocking. Binding affinities and key interactions were analyzed, followed by prediction of physicochemical properties, drug-likeness, and toxicity using ADMETlab 3.0 and ProTox-3.0. Docking results revealed that several compounds, including cerebrosides, lignans, and long-chain esterified phenolics, exhibited strong predicted binding to ACE. However, many high-affinity ligands showed unfavorable physicochemical characteristics, low quantitative estimates of drug-likeness, and multiple medicinal chemistry rule violations. In contrast, Piperenamide A and Piperenamide B demonstrated a balanced profile, combining stable ACE binding with favorable physicochemical properties, compliance with Lipinski’s Rule of Five, and low predicted toxicity. Simple phenolic compounds displayed good safety profiles despite moderate binding affinity. Overall, this integrative in silico analysis highlights compounds derived from Piper betle L. leaves as a promising natural source of ACE-inhibitory scaffolds and provides a rational framework for subsequent experimental validation and lead optimization in antihypertensive drug discovery.